Cover Feature: Single‐Molecule Magnet and Magnetothermal Properties of Two‐Dimensional Polymers Containing Heterometallic [Cu5Ln2] (Ln = GdIII and DyIII) Motifs (Eur. J. Inorg. Chem. 15/2018). Issue 15 (14th April 2018) - Dey, Atanu; Das, Sourav; Palacios, María A.; Colacio, Enrique; Chandrasekhar, Vadapalli
Abstract : The Cover Feature shows a two‐dimensional polymeric network containing [Cu5 Ln2 ] (Ln = Dy and Gd) motifs. The Dy‐analogue shows single‐molecule magnet (SMM) behavior, whereas the Gd‐analogue features the magnetocaloric effect. The picture on the top at the left is [Mn III 8 Mn IV 4 O12 (O2 CMe)16 (H2 O)4 ], the first known SMM. The mechanism of magnetic refrigeration by a gadolinium alloy implementing the magnetocaloric effect is illustrated at the bottom left. More information can be found in theFull Paper by E. Colacio, V. Chandrasekhar et al.